Coronavirus in pediatrics: report of two cases and review of the literature - Lucas R. Mostardeiro; Ellen Cristine A. Antoniolli; Jady W. Xavier
ABSTRACT COVID-19 was identified on December 31, 2019 in China, and has since been the subject of several studies. In the area of pediatrics, the infection appears to affect this population group more mildly when compared to adults. The present work shows the report of two cases of in patients in the pediatric age group, both aged 2 years, presenting their laboratory, clinical and radiological aspects. In this population, the virus's transmissibility seems to be related to symptom presentation, as the less symptomatic the patient presents the lower is transmissibility. The final interest of the presented cases is to demonstrate the good evolution that both patients in the pediatric age group showed, directing attention to the normality of laboratory tests and the presentation with a wide variety of differential diagnoses.